Institutional coordination arrangements as elements of policy design spaces - Lüpke, Heiner von; Leopold, Lucas; Tosun, Jale (Universität, 2023)
This study offers insights into the institutional arrangements established to coordinate policies aiming at the mitigation of and adaptation to cli...